Epigenetic silencing of HOPX contributes to cancer aggressiveness in breast cancer. (1st January 2017) - Kikuchi, Mariko; Katoh, Hiroshi; Waraya, Mina; Tanaka, Yoko; Ishii, Satoru; Tanaka, Toshimichi; Nishizawa, Nobuyuki; Yokoi, Keigo; Minatani, Naoko; Ema, Akira; Kosaka, Yoshimasa; Tanino, Hirokazu; et al.
Abstract: Epigenetic silencing of HOPX has been shown to be frequent and specific in human cancers. HOPX is thought as a tumor suppressor gene and its promoter methylation is the main mechanism of down-regulation. In non-hereditary breast cancer, since roles of epigenetic modifications are more critical than in other cancers, the aim of this study is to seek into the roles and clinical relevance of epigenetic silencing of HOPX. Down-regulation of HOPX was observed in all human breast cancer cell lines tested. The promoter methylation was found in six of seven cell lines, and demethylating agents restored HOPX expression. The promoter methylation was cancer-specific in human breast tissues. Forced expression of HOPX attenuated anchorage-independent growth in vitro . HOPX promoter methylation independently predicted worse prognosis of breast cancer patients. Of note, HOPX promoter methylation was significantly associated with HER2 positivity as well as advanced lymph node metastasis. HOPX promoter methylation is not only frequent and cancer-specific but also associated with aggressive phenotype in breast cancer. Epigenetic silencing of HOPX may have clinical potential as a biomarker in the treatment strategy of breast cancer patients. Highlights: Promoter methylation is the critical mechanism for epigenetic silencing of HOPX in breast cancer. HOPX promoter methylation is cancer-specific and frequent event in human breast cancer. HOPX promoter methylation independently predicts worse prognosis of breast cancer patients. HOPX promoter methylation was closely associated with HER2 positivity.